SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN ANGGOTA HIMPUNAN MAHASISWA JURUSAN TEKNIK INFORMATIKA DENGAN MENGGUNAKAN METODE ELECTRE (Studi Kasus : Sekolah Tinggi Teknologi Adisutjipto Yogyakarta) - Diana Corry; Yuliani Indrianingsih (Institut Teknologi Dirgantara Adisutjipto, 2014)
Himpunan Mahasiswa Jurusan (HMJ) is a student organization in the majors at the college level. HMJ Informatics is one of the HMJ on Sekolah Tinggi Teknologi Adisutjipto Yogyakarta. HMJ certainly has a vision and mission, therefore, to realize the vision and mission of the members is required in accordance with the criteria expected. There are several criteria for determining the decision-making division members HMJ. Criteria include interest, liveliness, confidence, psychology and CPI (Cumulative Performance Index). To resolve the issue it was made of Decision Support Systems (DSS) recruitment of HMJ division members using the method Elimination and Choice Expressing Reality (ELECTRE). The existences of these systems provide convenience to head of the HMJ to determine HMJ members. The system is built using the programming language Delphi 7 and Oracle databases. Based on calculations by the ELECTRE method obtained ranking prospective members. Taken example, 4 students applying to become a member of HMJ. Calculation shows Gilar Prakoso get ranked first by the number of assessment 4 percentage 80%, Koko Wiyono second ranked the number 2 percentage 40% assessment, Linda Putri Susanti third the number of ratings 1 percentage 20%, and Dini Larasati fourth the number of assessment - 7 the percentage of 0%. The calculations revealed that the results of the manual calculation in accordance with the results of the calculation system and can help the chairman HMJ decision in determining who is eligible to become a member.